THE RELATIONSHIP BETWEEN WORK-LIFE BALANCE AND JOB SATISFACTION AMONG EMPLOYEES IN PRIVATE SECTOR - Alexia, Liang (Universiti Malaysia Sarawak (UNIMAS), 2021)
The main purpose of this study is to identify the relationship between work-life balance and job satisfaction among employees in private sector. The independent variable which had been studied in this research is work-life balance which the component is workload and work role conflict, whereas the dependent variable is job satisfaction. A private sector organization is chosen for this present study. This study was conducted by using quantitative research methodology. The population for this study is 210 employees from three (3) private organizations. Then, the sample size was chosen based on simple random sampling. A survey questionnaire had been used to collect data from respondents for this study. It further analyzed using „Statistical Package for Social Science‟ (SPSS) version 22.0. Moreover, descriptive statistics were used to analyze the demographic background of respondents which includes gender, age, marital status, length of service, education level, job position and job status. Pearson Correlation and Multiple Regression were used to analyze and identify the relation between independent variables and dependents variables. The findings indicated that there is a significant negative relationship between worklife balance which the component is workload and work role conflict with job satisfaction among employees in private sector. The result also indicates that there is the dominant factor affecting job satisfaction where work-life balance component which is workload stronger than work role conflict on negatively affecting job satisfaction among employees in private sector. Lastly, recommendations and suggestions had been proposed for future reference of organization, Human Resource practitioner and future research.